Heralding manifestations of basilar artery occlusion with lethal or severe stroke. Issue 12 (24th November 2003) - von Campe, G; Regli, F; Bogousslavsky, J
Abstract : Background: Basilar artery occlusion usually causes severe disability or death. Until the recent developments in local intra-arterial or systemic intravenous fibrinolysis, interest in early diagnosis was low because there was no satisfactory treatment. Thus there is little information about the initial phase of the disease. Objective: To report on the early clinical features and patterns of evolution of severe symptomatic basilar artery occlusion. Methods: 24 patients with established basilar artery occlusion (confirmed by angiography or at necropsy) were reviewed retrospectively, focusing on the early clinical aspects and time course of the disease. Results: The most common initial symptoms were motor deficits (16/24, including facial palsies), articulatory speech difficulties (15/24), vertigo, nausea or vomiting (13/24), and headaches (10/24). The most frequent objective initial findings were motor deficits (22/24), facial palsies (19/24), eye movement abnormalities (15/24), lower cranial nerve deficits (15/24), altered level of consciousness (12/24), and bilateral extensor plantar responses (9/24). Onset of the disease was gradual in nearly all patients and in half the warning signs were present for up to two months before the final stage. Headaches and visual disturbances were early signs, while speech difficulties and motor deficits were late signs. Once permanent neurological deficits were present, the final illness was reached within six hours in 41%, between six and 24 hours in 32%, and in two to three days in 27%. Conclusions: All the patients reviewed presented some symptoms and signs pointing to brain stem involvement. Only 8% (2/24) had an acute course with no adequate warning signs.